Translingual practice as a rhetorical tactic in the 2024 gubernatorial election debates - Umam, Akhmad Hairul; Sugiharto, Setiono; Nisa, Baiatun (UNIB Press, 2025)
With an emphasis on the overall rhetorical tactics used in a political discourse, this qualitative case study investigates translingual practice in the 2024 Jakarta gubernatorial election debates. It specifically examines how the candidates deliberately switched between Indonesian, English, and regional languages to interact with a linguistically varied population and to create compelling political narratives. The study is framed under the frameworks of both translingualism and Critical Discourse Analysis (CDA). Data sources were taken from the transcribed video recordings. The analysis emphasizes the interplay between multilingual communication, voter perception, and identity construction within Jakarta’s multicultural context. The findings revealed that translingual practice was purposefully used to appeal to a broader range of demographic groups. Candidates can improve their political messaging, negotiate their identities, and promote inclusivity by mixing languages. Translingual practice is a dynamic and flexible tool for political communication in Jakarta's diverse language environment. By showing that translingual practice serves as a strategic performative tool in electoral engagement rather than just being a reflection of Indonesia's linguistic diversity, this study contributes to the body of research on political discourse in multilingual cultures. It makes the case that, especially in globalized metropolitan contexts, language choice in political discourse is vital for influencing public opinion and for navigating democratic processes.